2020
DOI: 10.3390/nu12010238
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Advanced Glycation End Products in Patients with Newly Diagnosed Versus Established Diabetes: From the CORDIOPREV Study

Abstract: Endothelial dysfunction and intima-media thickness of common carotid arteries (IMT-CC) are considered subclinical markers of atherosclerotic cardiovascular disease (ASCVD). Advanced glycation end products (AGEs) are increased in type 2 diabetes mellitus (T2DM) patients, compared with non-diabetics, being implicated in micro- and macrovascular complications. Our aim was to compare serum AGEs levels and subclinical atherosclerotic markers between patients with established and newly diagnosed T2DM. Among 540 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…At the same time, FMD is also an important assessment method of target organ injury. [7] baPWV is another main index to detect the degree of arteriosclerosis, and its change is the overall reflection of abnormal structure and function of arteries. The results showed that baPWV was an independent predictor of hypertension, and the risk ratio of baPWV increased by 1…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
“…At the same time, FMD is also an important assessment method of target organ injury. [7] baPWV is another main index to detect the degree of arteriosclerosis, and its change is the overall reflection of abnormal structure and function of arteries. The results showed that baPWV was an independent predictor of hypertension, and the risk ratio of baPWV increased by 1…”
Section: Journal Of Translational Internal Medicine / Aopmentioning
confidence: 99%
“…Previous studies have indicated that AGEs intake may be implicated in non-communicable diseases such as diabetes, 31,32 chronic kidney disease, 33 non-alcoholic fatty liver disease, 34 coronary heart disease, 32 obstructive airway diseases, 35 cancer, 36 dementia and aging, 37 arthritis, 38 asthma/wheeze 39,40 and chronic bronchitis. 37,[41][42][43] Studies focusing on allergy outcomes, showed an association between the childhood diet, studied at a similar time as allergic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in findings between our study and previous studies may also be explained by different measures and methods used to determine AGEs intake or different methods for assessment of allergy outcomes. Previous studies investigating the association between AGEs and disease outcomes used serum levels of AGEs, 31,46 or activity of the age receptor (RAGE) 37,42,43 rather than dietary intake of AGEs as in our study. Some studies measured reported highfructose corn syrup-sweetened soft drinks, fruit drinks, 38 apple juice, and soda intake.…”
Section: Discussionmentioning
confidence: 99%
“…Накопление конечных продуктов гликирования при прогрессировании диабета способствует структурному ремоделированию сосудистой стенки, что проявляется, в частности, увеличением толщины интимы и медии сонных артерий [51].…”
Section: роль неферментативного гликозилирования в развитии сосудистых осложнений сахарного диабетаunclassified